Formation of pulses with controlled parameters in a resonance microwave compressor employing oscillation-mode transformation; Technical Physics Letters; Vol. 39, iss. 9 - Avgustinovich V. A. Vladimir Andreevich; Artemenko S. N. Sergey Nikolaevich; Igumnov V. S. Vladislav Sergeevich; Yushkov Y. G. Yuri Georgievich (2013, 2013)
Title screen